Ovis dalli Nelson 1884 - Peter Grubb (Smithsonian Institution Press, 1993)
Ovis dalli Nelson, 1884. Proc. U.S. Natl. Mus., 7: 13. TYPE LOCALITY: Alaska, west bank of Yukon River, Tanana Hills. DISTRIBUTION: Alaska to N British Columbia and W Mackenzie (Canada). SYNONYMS: cowani, fannini, kenaiensis, liardensis, niger, stonei. COMMENTS: Revised by Cowan (1940). Reviewed by Bowyer and Leslie (1992, Mammalian Species, 393). Published as part of Peter Grubb, 1993, Order Artiodactyla, pp. 377-414 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 409, DOI: 10.5281/zenodo.7359189